2019
DOI: 10.1186/s12893-018-0465-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy of primary hepatic angiosarcoma

Abstract: BackgroundPrimary hepatic angiosarcoma (PHA) is a rare tumor entity. Radical surgical resection is currently considered the best treatment choice. The aim of this analysis is to report our experience with surgery for PHA.MethodsAll resections of PHA from 01/2002 until 06/2017 were identified from our prospective institutional database. All cases were re-confirmed by a second pathologist. We analyzed completeness of resection, overall (OS) and disease-free survival (DFS).ResultsNine patients with PHA underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…31 Currently, radical surgical resection is considered the treatment of choice for primary hepatic angiosarcoma in humans. 40 In one study of 9 patients who underwent hepatic resection for primary hepatic angiosarcoma, median overall survival and disease-free survival were 59 and 11 mo, respectively. 40 However, the tumors in all 9 patients were histologic grade II, meaning that a patient who had metastases similar to the animal we described here (that is, grade III) would be a poor candidate for surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Currently, radical surgical resection is considered the treatment of choice for primary hepatic angiosarcoma in humans. 40 In one study of 9 patients who underwent hepatic resection for primary hepatic angiosarcoma, median overall survival and disease-free survival were 59 and 11 mo, respectively. 40 However, the tumors in all 9 patients were histologic grade II, meaning that a patient who had metastases similar to the animal we described here (that is, grade III) would be a poor candidate for surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…40 In one study of 9 patients who underwent hepatic resection for primary hepatic angiosarcoma, median overall survival and disease-free survival were 59 and 11 mo, respectively. 40 However, the tumors in all 9 patients were histologic grade II, meaning that a patient who had metastases similar to the animal we described here (that is, grade III) would be a poor candidate for surgical resection. For advanced disease, chemotherapy currently offers minimal benefit in terms of survival time, with a few exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in which 6 patients received transcatheter arterial chemoembolization or transcatheter arterial embolization alone for hepatic angiosarcoma resulted in all patients expiring within 1 year[ 11 ]. A recent study of 8 patients with R0-resected hepatic angiosarcoma showed median survival and disease-free survival of 59 and 11 mo which emphasizes the radical surgical resection is best approach for long-term survival[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There did not appear to be a standard surgical approach, with similar proportions of wedge resection (33%), lobectomy (29%), and transplantation (29%) in patients with angiosarcoma and wedge resection (39%) or transplantation (39%) in patients with EHE. The extent of resection performed varies in the literature, but a report from Tripke et al advocates for anatomical hemihepatectomy or radical hepatectomy for curative intent in angiosarcoma 27 . Their report also stressed the importance of R0 resection, as the nine patients that achieved this result had a median overall survival of 59 months.…”
Section: Discussionmentioning
confidence: 99%
“…a Percentages are calculated per category, as not all patients had data for each category.F I G U R E 1Overall survival for pediatric and adult patients with hepatic vascular malignancies (P < .001)F I G U R E 2Overall survival for all patients with ([2-40], P = .09). Finally, there was a significantly longer mean overall survival (95% CI) for angiosarcoma tumors <10 cm versus ≥10 cm (23 months[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] vs 12 months[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], P = .001).The mean overall survival (95% CI) for all patients with EHE was 98 months (87-109). Similar to angiosarcoma, survivorship for patients with EHE improved if surgical resection was performed (122 months F I G U R E 3 Overall survival of all patients with (A) angiosarcoma and (B) malignant epithelioid hemangioendothelioma who received surgical treatment alone versus surgical and chemotherapeutic treatment versus chemotherapeutic treatment alone (P < .0001)[107-136]), and was worse if resection was not performed (…”
mentioning
confidence: 99%